Isolation of Usutu virus in Germany - Jöst, Hanna; Bialonski, Alexandra; Maus, Deborah; Sambri, Vittorio; Eiden, Martin; Groschup, Martin H.; Günther, Stephan; Becker, Norbert; Schmidt-Chanasit, Jonas (The American journal of tropical medicine and hygiene, 2011)
Usutu virus (USUV) is a mosquito-borne flavivirus that emerged 2001 in Austria and caused deaths in wild birds. In Germany, 70,378 female mosquitoes were captured in 2009 and 2010 and assayed for USUV. Virus was isolated in cell culture from one pool of Culex pipiens pipiens mosquitoes trapped exclusively in August 2010 in Weinheim, Germany. Subsequent phylogenetic analysis demonstrated a close relationship between the isolated USUV strain from Germany and a USUV strain from Austria, which was detected in a dead blackbird in 2004.
Gesehen am 05.07.2022